Status, ecology and conservation of Irrawaddy dolphins (Orcaella brevirostris) in Malampaya Sound, Palawan, Philippines - Smith, Brian D.; Beasley , Isabel; Buccat , Mariel; Calderon , Victor; Evina , Roderick; de Valle , Joseph Lemmuel; Cadigal , Angela; Tura , Emmalyn; Visitacion , Zhuljakim (J. Cetacean Res. Manage., 2023)
A geographically isolated population of Irrawaddy dolphins was recently discovered in Malampaya Sound, Palawan, Philippines. Line-transect surveys conducted in April-November 2001 covered 884km of trackline in the entire Sound and resulted in a total population estimate of 77 individuals (CV = 27.4%), confined to the inner portion (133.7km2 ). For all Irrawaddy dolphin sightings, where ecological data were collected (n = 48), the mean temperature was 30.2°C, depth 6.5m, salinity 28.3ppt and turbidity 2.2NTUs. Significantly higher turbidity, lower salinity and shallower depth were recorded in the inner Sound compared to adjacent waters. Bottlenose dolphins Tursiops sp. (probably truncatus) were observed in waters just outside of where Irrawaddy dolphins were recorded. During the study, at least two Irrawaddy dolphins were accidentally killed in bottom-set nylon gillnets used to catch crabs, locally called matang quatro. Reports from local fishermen also indicated that as many as three additional animals may have been killed in these nets during the same period. These findings strongly suggest that the Irrawaddy dolphin population in Malampaya Sound is in immediate danger of extirpation due to low numbers, limited range and high mortality. This is the only known population of the species in the Philippines and the nearest known other population is in northern Borneo, some 550km to the south. Recommendations for conserving the population include that: (1) socioeconomic alternatives be developed to promote the conservation goal of reducing the incidence of dolphin entanglement in matang quatro gillnets; (2) gillnet free zones be established in core areas of dolphin distribution; (3) Irrawaddy dolphins be promoted as a flagship species of environmental health in the Sound; (4) a long-term programme be established to monitor the dolphin population; and (5) additional investigations be conducted to determine if Irrawaddy dolphins occur in other areas of the Philippines.